2020
DOI: 10.1111/den.13684
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for endoscopic diagnosis of early gastric cancer

Abstract: The Japan Gastroenterological Endoscopy Society developed the Guideline for Endoscopic Diagnosis of Early Gastric Cancer based on scientific methods. Endoscopy for the diagnosis of early gastric cancer has been acknowledged as a useful and highly precise examination, and its use has become increasingly more common in recent years. However, the level of evidence in this field is low, and it is often necessary to determine recommendations based on expert consensus only. This clinical practice guideline consists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 221 publications
2
163
0
4
Order By: Relevance
“…In Japan, systematic screening of the stomach (SSS) is an alternative method to exclusively screen the stomach with 22 images without documenting the EGJ and the pyloric channel. 31 The systematic exam herein described differs from the SSS proposal in its overlapped non-blind regions characteristics and its alphanumeric code system. Noteworthily, gastric SACE is, in practice, part of a complete system evaluation of the upper GI tract, which includes the pharynx, the esophagus, and the duodenum 3,8 (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In Japan, systematic screening of the stomach (SSS) is an alternative method to exclusively screen the stomach with 22 images without documenting the EGJ and the pyloric channel. 31 The systematic exam herein described differs from the SSS proposal in its overlapped non-blind regions characteristics and its alphanumeric code system. Noteworthily, gastric SACE is, in practice, part of a complete system evaluation of the upper GI tract, which includes the pharynx, the esophagus, and the duodenum 3,8 (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The stomach is an organ with a wide, curved lumen, and there are blind spots in the stomach even when the entire stomach is examined. 13 If AI can recognize the anatomical regions of the stomach, it can be confirmed that the entire stomach was comprehensively examined. Takiyama et al 14 introduced an AI system based on the images from EGD, to divide the upper gastrointestinal tract into the pharynx, esophagus, upper stomach, middle stomach, lower stomach, and duodenum ( Fig.…”
Section: Anatomical Classification Of Stomachmentioning
confidence: 99%
“…Inadequate examination of the stomach is one of the reasons for missing the GC on endoscopy. The stomach is an organ with a wide, curved lumen, and there are blind spots in the stomach even when the entire stomach is examined 13 . If AI can recognize the anatomical regions of the stomach, it can be confirmed that the entire stomach was comprehensively examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good demarcation was defined when any of the followings were met: presence of a demarcation line and color change of tumor compared to background mucosa. 15,16 Atrophic gastritis was described according to Kimura-Takemoto classification. 17 Intestinal metaplasia was determined as the presence of whitish or erythematous nodular lesions and/ or presence of blue light crest on narrow band imaging.…”
Section: Endoscopic Assessment and Resectionmentioning
confidence: 99%